Expression of the human EPO gene in banana (Musa acuminata) / Geradline Joanne Fernando - Geradline Joanne, Fernando (2008)
Erythropoietin (EPO) is a glycoprotein hormone which plays a vital role in the regulation of the formation of red blood cells in mammals. Inadequate production of EPO was found to be one of the major causes of anaemia. Anaemia is also a frequent complication to many other diseases such as AIDS, chronic renal failure, rheumatoid arthritis, etc. In the mid-1980s, anaemia was treated with blood transfusion which however brought about many other problems. The advent of recombinant DNA technology proved to be a useful method for the mass production of recombinant EPO. However, finding a stable biofactory for the production of this protein was essential as the expression system needed to have certain attributes for the large and safe production of EPO. In this proof of concept experiment, the use of banana (Musa acuminata) has shown to be of great potential as an expression system for the production of recombinant EPO. Particle bombardment was also a suitable transformation method for the transient expression of the EPO gene. The transformation success of about 17-80% success (based on GFP expression and RT-PCR results) proved that meristems of banana were able to express the human EPO gene in its system in the period studied. Nevertheless, the production of the recombinant protein appeared to have stunted the growth of the banana plant and decreased the number of multiple shoots formed from the meristem compared to the controls. The use of the KDEL sequence in the gene construct potentially enables the retention of the EPO protein in the endoplasmic reticulum for higher expression levels. This study however did not analyse the expression levels of EPO with and without the KDEL in its construct. However, the transcription of EPO in both the constructs was observed based on the RT-PCR results further suggesting the successful transformation of the cells. This study shows that the ii human EPO gene can be transformed in banana meristems and the EPO mRNA in the transformants were also shown to be successfully transcribed.